2011
DOI: 10.1021/np100902f
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Principles from Cordyceps sinensis

Abstract: In order to explore the anti-inflammatory principles of the mycelia of Cordyceps sinensis, the crude extract and partially purified fractions were examined for their inhibition of superoxide anion generation and elastase release. Further chemical investigation of the bioactive fractions has resulted in the identification of 50 compounds, including five constituents, cordysinins A-E (1-5), reported from a natural source for the first time. In addition, compounds were examined for their anti-inflammatory activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(62 citation statements)
references
References 18 publications
0
61
0
1
Order By: Relevance
“…As inflammation is also one of the hallmark of aging (Zhang et al 2013a) and presence of compounds like ergosterol peroxide (2), ergosteryl-3-O-â-Dglucopyranoside (4), stigmasterol (10), cordycepin (13), perlolyrine (17), and cordymin (18) with the antiinflammatory property can have role in anti-ageing effect of O. sinensis. Cordycepin is one of the most active compound with several activities (Yun et al 2003, Kim et al 2006, Holliday & Cleaver 2008, Yue et al 2008, Kim et al 2009, Leu et al 2011, Yang et al 2011, Xiao et al 2012. There is possibility of its role in synergetic effect with other compounds for several therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As inflammation is also one of the hallmark of aging (Zhang et al 2013a) and presence of compounds like ergosterol peroxide (2), ergosteryl-3-O-â-Dglucopyranoside (4), stigmasterol (10), cordycepin (13), perlolyrine (17), and cordymin (18) with the antiinflammatory property can have role in anti-ageing effect of O. sinensis. Cordycepin is one of the most active compound with several activities (Yun et al 2003, Kim et al 2006, Holliday & Cleaver 2008, Yue et al 2008, Kim et al 2009, Leu et al 2011, Yang et al 2011, Xiao et al 2012. There is possibility of its role in synergetic effect with other compounds for several therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2009) reported two new epipolythio dioxopiperazines, gliocladicillins A, B and 11,112 -dideoxyverticillin from Cordyceps-associated fungi which indicated possibly beneficial O. sinensis associated species. Yang et al (2011) isolated 50 compounds, including five new constituents, cordysinins A-E. Yu et al (2012) reported fifty-one volatile compounds including aldehydes, alcohols, ketones, esters, aromatics, phenols, acids, alkanes, alkenes, furans and other phenolic compounds from the mycelia cultured by solid-state media and submerged fermentation. Although there are several possibilities of synergetic relation of compounds working to give some activities, the lock-and-key theory and one hit target to combat certain disease is required in practice for effective use of well defined drugs, their production and commercialization for the benefit of mass population.…”
Section: Introductionmentioning
confidence: 99%
“…Major phytochemical constituents of O. sinensis are (i) Proteins: cadaverine, spermidine, spermine, putrescine, flazin, perlolyrine, methylpyrimidine, carboline, cordymin, tryptophan (Zhang et al, 1991;Qian et al, 2012;Wang et al, 2012); (ii) Nitrogenous compounds: uracil, adenine, gunine, hypoxanthine, adenosine, cordycepin, dideoxyadenosine, inosine, guanosine, thymine, thymidine, uridine, cordyceamides, cordysinin (Zhu et al, 1998a, Huang et al, 2004, Jia et al, 2009(iii) Sterols: ergosterol, sitisterol, daucosterol, stigmasterol, cholesterol, campesterol (Bok et al, 1999); (iv) Fatty acids: palmitic acid, lauric acid, myristic acid, pentadecanoic acid, palmitoleic acid, linoleic acid, oleic acid, stearic acid, docosanoic acid, lignoceric acid, succinic acid (Yang et al, 2009); (v) Phenolic acids: hydroxybenzoic acid, vanillic acid, syringic acid, protocatechuic acid, acetovanillone, salicylic acid (Yang et al, 2011); (vi) Isoflavones: glycitein, daidzein, orobol, genistein (Yang et al, 2011); (vii) Polysaccharides and sugar derivatives: glucan, cordysinocan, mannoglucan, mannitol (Wu et al, 2007;Zhong et al, 2009;Yang et al, 2011); (viii) vitamins, inorganics and volatile compounds (Zhu et al, 1998a and1998b;Yu et al, 2012).…”
Section: Phytochemical Substancesmentioning
confidence: 99%
“…sinensis is traditionally used (Wang and Shiao, 2000;Seth et al, 2014) for anti-inflammation (Yang et al, 2011;Wang et al, 2012), antimicrobial activity (Negi et al, 2014;Mamta Mehrotra et al, 2015), antidiabetic (Kiho et al, 1999;Balon et al, 2002;Lo et al, 2004;Li et al, 2006;Zhang et al, 2006;Shi et al, 2009;El Ashry et al, 2012), antitumor activity (Bok et al, 1999;Zhang et al, 2004), antimetastatic (Nakamura et al, 1999), immunomodulatory (Gong et al, 1990), hypocholesterolemia (Koh et al, 2003), and antioxidant activities (Yamaguchi et al, 2000;Li et al, 2002;Dong and Yao, 2007;Wang et al, 2009), and associated diseases such as hepatic diseases (Liu and Shen, 2003) and chronic kidney diseases . Meena et al (2013) reported that laboratory cultured mycelia powder of O. sinensis is safe and non-toxic up to 2g/kg body weight dose.…”
Section: Traditional Usesmentioning
confidence: 99%
“…[2] The C-domain of the nonribosomal peptide synthetase SfmC from Streptomyces lavendulae also is known to mediate PS cyclization during the course of saframycin biosynthesis. [3] There exists a small group of C-ring unsaturated bCs in which C1 is substituted by a two-carbon unit found in various organisms, including medicinal plants, [4] marine tunicate, [5] fungi, [6] and actinomycetes (Scheme 1). [7] Such compounds have attracted significant interest from synthetic chemists.…”
mentioning
confidence: 99%